OPTIMASI PENGOLAHAN TEH HERBAL POKAK (SOLANUM TORVUM) METODE RESPON PERMUKAAN (RESPONSE SURFACE METHODHOLOGY- BOX BEHNKEN DESIGN) - Nunuk Helilusiatiningsih; Titik Irawati (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2021)
Pokak eggplant (Solanum torvum), which is spread throughout Indonesia, was a useful herbal medicine. The use of pokak eggplant, which had another name, eggplant or takokak, had not been widely marketed in supermarkets or traditional markets. Raw materials were classified as wild because they have not been widely cultivated, so new innovation technology was needed to process pokak eggplant fruit into herbal teas that were economically beneficial and health and long lasting. The research objective was to determine the optimization of the processing of pokak eggplant fruit into herbal tea products. The research method used the response surface (Response Surface Methodology Box Behind Desaint). There are 4 stages of processing pokak eggplant herbal tea including curing, fermentation, temperature and drying time. The observed parameters of treatment response included 4 components of phytochemical compounds analyzed, namely antioxidant activity (% DPPH absorption), total phenol content, tannin content, and flavonoid levels. The results showed that the optimal processing conditions were obtained in the processing of pokak herbal tea on curing for 4.8 days at room temperature, fermentation for 6 hours 18 minutes and a vacuum drying temperature of 49.95oC and a drying time of 14 hours. Pokak herbal tea produced under the optimum process conditions of verification results had antioxidant activity (% DPPH inbibition), total phenol content, tannins and flavonoids respectively 85.77%, 65.50 mg / g, 1.95 mg / g and 4, 48 mg /g.